Effect of narrative writing based on Gibbs’ reflective model on the empathy and communication skills of nursing students - Najmeh Ahmadpour; Atefeh Shariati; Mahdieh Poodineh Moghadam (BMC Medical Education)
Abstract Background One of the essential skills required in nursing students is empathetic communication and communication skills. Communication skills refer to a set of potential and actual abilities that help achieve acceptable and informative behavior, leading to a level of emotional connection. This interpersonal skill facilitates the establishment and strengthening of the nurse-patient relationship. Therefore, researchers aimed to conduct a study to determine the impact of narrative writing based on Gibbs’ reflective model on the empathy and communication skills of nursing students. Methods This quasi-experimental research was conducted using two groups and before-after design. The statistical population consisted of all third and fourth-year nursing students at Zabol University of Medical Sciences in 2023, among whom 80 students were selected by the census. The data collection tools included a demographic information form and reliable and valid questionnaires for empathy and communication skills. In the intervention group, Gibbs’ reflective thinking was taught through workshops. Students in this group were asked to engage in narrative writing-reflection sessions for 8 weeks, producing at least 8 narratives (one at the end of each week). The empathy and communication skills questionnaires were completed again at the end of the 8th week. The obtained data were analyzed using SPSS software (version 22), applying descriptive statistics and inferential statistics at a significance level of p ≤ 0.05 and a 95% confidence interval. Results The results of this study indicate that narrative writing based on Gibbs’ reflective model can positively impact nursing students’ empathy and communication skills. Specifically, the mean empathy score in the intervention group increased from 63.35 ± 6.61 to 70.20 ± 10.43, which was statistically significant according to the paired t-test (P = 0.000). In contrast, the control group showed no significant change in empathy, with scores changing from 62.70 ± 8.20 to 62.72 ± 7.92 (P = 0.760). Similarly, the mean communication skill in the intervention group improved from 183 ± 16.15 to 211.75 ± 9.30, with this change also being statistically significant (P = 0.000). In the control group, communication skills changed minimally from 186.27 ± 16.07 to 187.60 ± 15.44, which was not statistically significant (P = 0.215). Furthermore, when comparing the changes in empathy and communication skill scores according to demographic and educational variables, no significant differences were found (P > 0.05). Conclusions Narrative writing helps students establish a more appropriate relationship with patients by fostering a deeper understanding of their issues and enhancing their empathy, leading to better patient care during their treatment. This suggests that incorporating narrative writing into nursing education could be beneficial for developing essential skills in future healthcare professionals.